O’ZBEKISTONNING JAHON SAVDO TASHKILOTIGA A’ZO BO’LISHINING O’ZIGA XOS JIHATLARI - Islamova Barnoxon Axrorjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Uzbekistan's membership in the World Trade Organization (WTO) is an important step towards the country's integration into the world economic system. This article examines the unique characteristics, challenges and opportunities that Uzbekistan faces in its accession process. The study examines Uzbekistan's economic profile, trade policy, institutional reforms, and the possible impact of WTO membership on its economy, focusing on agriculture, industry, and service sectors.